Online chatting system for online community system / Lim Boon Hong - Lim, Boon Hong (2002)
Online Community is a web application that provides a complete and efficient communication environment for the online user. Any online user can create a community to connect a group of online users. Therefore, online user can create a private area to share their information and knowledge with other online user in the secure environment. Online community can be divided into 3 main modules Online Information System, Administration System and Online Chatting System. This project is focus on the on the Online Chatting System. Online Chatting System is a java Chat application that based on the Online Community. The main purpose of online chatting system is providing a chatting environment for community member. Group meeting can take place in real time using Online Chatting System. The Online Chatting System will enable the Community member to have a more pleasant charting environment by leveraging on the benefits of the Internet to provide a virtual discussion place on World Wide Web. Online Chatting System can be divided into 2 main users ordinary member and administrator (normal administrator and super administrator). The ordinary member is the member join the community and their function is limited. An ordinary community member can have public chat, private conversation and view the other member profile function. In the administrator side, the administrator can different into normal administrator and super administrator. The normal administrator is also called Community Manager or Chat Master. The normal administrator is the community member who firstly creates the community. The normal administrator has more powerful function and privilege, A normal administrator can have public chat, private conversation, Chat watch, Chat Broadcast, Chat Monitor, kick and ban ordinary users. The Super administrator is along Online Chatting System Server on the same host. Therefore, super administrator has most powerful function to maintain the Online Community web site's performance. A Super administrator also called Chat Commander in the Online Chatting System.